Clostridium butyricum, a butyrate-producing probiotic, inhibits intestinal tumor development through modulating Wnt signaling and gut microbiota - Chen, Danfeng; Jin, Duochen; Huang, Shumin; Wu, Jingyi; Xu, Mengque; Liu, Tianyu; Dong, Wenxiao; Liu, Xiang; Wang, Sinan; Zhong, Weilong; Liu, Yi; Jiang, Ruihuan; et al. (Cancer letters, 2020)
Gut microbiota dysbiosis is closely involved in intestinal carcinogenesis. A marked reduction in butyrate-producing bacteria has been observed in patients with colorectal cancer (CRC); nevertheless, the potential benefit of butyrate-producing bacteria against intestinal tumor development has not been fully investigated. We found that Clostridium butyricum (C. butyricum, one of the commonly used butyrate-producing bacteria in clinical settings) significantly inhibited high-fat diet (HFD)-induced intestinal tumor development in Apcmin/+ mice. Moreover, intestinal tumor cells treated with C. butyricum exhibited decreased proliferation and increased apoptosis. Additionally, C. butyricum suppressed the Wnt/β-catenin signaling pathway and modulated the gut microbiota composition, as demonstrated by decreases in some pathogenic bacteria and bile acid (BA)-biotransforming bacteria and increases in some beneficial bacteria, including short-chain fatty acid (SCFA)-producing bacteria. Accordingly, C. butyricum decreased the fecal secondary BA contents, increased the cecal SCFA quantities, and activated G-protein coupled receptors (GPRs), such as GPR43 and GPR109A. The anti-proliferative effect of C. butyricum was blunted by GPR43 gene silencing using small interfering RNA (siRNA). The analysis of clinical specimens revealed that the expression of GPR43 and GPR109A gradually decreased from human normal colonic tissue to adenoma to carcinoma. Together, our results show that C. butyricum can inhibit intestinal tumor development by modulating Wnt signaling and gut microbiota and thus suggest the potential efficacy of butyrate-producing bacteria against CRC. •CB inhibited intestinal tumor development via modulating Wnt signaling.•CB altered gut microbiota and microbial-derived metabolites levels.•GPR43 and GPR109A were involved in the efficacy of CB.